FREQUENCY OF LEFT DISPLACEMENT OFABOMASUM IN DAIRY COWS IN THE LIMA REGION - Silva G., David A. (2011)
The objective of the present study was to determine the frequency of left displacement of the abomasum in dairy cows in 10 farms of the Lima region between years 2000 to 2004. The frequency occurrence was 6‰ (121 cases within 20 131 parturitions), where the largest number of cases occurring during the 2nd and 4th week after calving. Also, 74% of affected cows were sent to the slaughterhouse.